Pendampingan dan Peningkatan Pemahaman Akreditasi Di SMP-Qur’an Dan SMK-Qur’an Pondok Pesantren Darul Ma’arif Nahdlatul Ulama Rejang Lebong - Rahman Arifin; Mabrur Syah; idwal idwal; Hendri Kusmidi; Lendrawati Lendrawati; Asnaini Asnaini; Jarot Wahyudi (Institut Agama Islam Negeri Bengkulu, 2023)
This abstract discusses the Asset Based Community Development (ABCD) Method approach in overcoming the problem of unaccredited SMP and SMK Quran NU Rejang Lebong in Rejang Lebong area. The phenomenon of this problem is felt by SMP and SMK Quran Darul Ma'arif NU Rejang Lebong, which have difficulty obtaining official accreditation. The purpose of this research is to provide an assistance mechanism for proposing the accreditation status of SMP and SMK Quran Darul Ma'arif NU Rejang Lebong through the application of the ABCD method. This ABCD approach aims to identify and optimise the potential and resources that exist in the surrounding community. This method focuses on the utilisation of existing potential and resources in the community, such as community knowledge and skills, social relations, and physical assets that can be utilised to improve the quality of education. The results of this research are expected to contribute to improving the quality of Quranic junior high school and vocational school education. By assisting the proposal for accreditation status through the ABCD method, the Darul Ma'arif NU Rejang Lebong Quran Junior High School and Vocational School will become accredited schools, able to provide quality education, and provide greater benefits to the surrounding community.